Creating prosocial environments in prison: Insights from the lived experiences in character-based units - Smith, Hayden (Criminal justice studies, 2024)
This study examines the role of Character-Based Units (CBUs) in facilitating rehabilitation among incarcerated populations within a Southeastern U.S. prison system. A sample of 316 participants from three correctional facilities was analyzed to evaluate the impact of CBUs on various behavioral and emotional outcomes. Utilizing a survey methodology, the research assessed shifts in deviant behavior, emotional well-being, and coping mechanisms before and after participants engaged with the CBU environment. The results indicate notable changes in self-reported deviance, with a significant decrease in the prevalence of deviant thoughts and associations with antisocial peers. Furthermore, emotional health metrics revealed that a substantial majority of participants exhibited strong perspective-taking abilities and positive affective responses. Stress levels were reported as low, with a high percentage of individuals demonstrating effective coping skills. These findings suggest that CBUs may effectively promote prosocial behavior and emotional resilience among incarcerated individuals, positioning them as a promising alternative to conventional rehabilitation programs. Future research is encouraged to investigate the long-term effects of CBUs on the overall well-being of those involved over time.